Longitudinal Analysis of Human Memory T-Cell Response According to the Severity of Illness up to 8 Months After Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (23rd March 2021) - Kang, Chang Kyung; Kim, Minji; Lee, Soojin; Kim, Gwanghun; Choe, Pyoeng Gyun; Park, Wan Beom; Kim, Nam Joong; Lee, Chang-Han; Kim, Ik Soo; Jung, Keehoon; Lee, Dong-Sup; Shin, Hyun Mu; et al.
Abstract: Background: Understanding the memory T-cell response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is crucial for assessing the longevity of protective immunity after SARS-CoV-2 infection or coronavirus disease 2019 (COVID-19) vaccination. However, the longitudinal memory T-cell response up to 8 months post–symptom onset (PSO) according to the severity of illness is unknown. Methods: We analyzed peripheral blood mononuclear cells (PBMCs) from healthy volunteers or patients with COVID-19 who experienced asymptomatic, mild, or severe illness at 2, 5, and 8 months PSO. SARS-CoV-2 spike, nucleocapsid, and membrane protein-stimulated PBMCs were subjected to flow cytometry analysis. Results: A total of 24 patients (7 asymptomatic, 9 with mild disease, and 8 with severe disease) and 6 healthy volunteers were analyzed. SARS-CoV-2–specific OX40 + CD137 + CD4 + T cells and CD69 + CD137 + CD8 + T cells persisted at 8 months PSO. Also, antigen-specific cytokine-producing or polyfunctional CD4 + T cells were maintained for up to 8 months PSO. Memory CD4 + T-cell responses tended to be greater in patients who had severe illness than in those with mild or asymptomatic disease. Conclusions: Memory response to SARS-CoV-2, based on the frequency and functionality, persists for 8 months PSO. Further investigations involving its longevity and protective effect from reinfection are warranted. Abstract : Flow cytometric analyses showed frequent and functional memory T-cell response to severe acute respiratory syndrome coronavirus 2 for 8 months post–symptom onset. Memory CD4 + T-cell response tended to be greater in severe patients than in mild or asymptomatic patients.